Improving the delivery of extension services in the Philippines lessons learned and future directions - Ocenar, Remigio D.; Brillantes, Alex B., Jr.; Cuthbertson, Sandy; Tumanut, Michael A. (2004)
Agricultural productivity improvements are essential for achieving overall economic growth. The Philippine performance on both counts has been disappointing. Agricultural extension which is one way of improving productivity has undergone substantial change in the last thirteen years through devolution under the Local Government Code of 1991. Whether devolution has improved agricultural extension delivery is a key question. Devolution generally has yielded some positive outcomes: cooperation between local government units (LGUs) and with the private sector and nongovernment organizations (NGOs); recognition of the realities of globalization; and use of modern management and communication. But problems of capacity building, partisan local politics and uncertain lines of financial and decisionmaking accountability between central and local government remain. These general lessons apply to agricultural extension. Moreover, even the best extension service, whether delivered where farmer decisionmaking is unduly influenced by government controls and pricing policies and where security of tenure is weak.
Keywords: Agricultural productivity; Agricultural extension work -- Case studies